The Penile Fracture, Surgical Outcome, and Post-operative Complications - Javed Altaf Jat, Tamoor Jatoi, Ihsan Ullah Khan, Ahsan Ali Arain, Maryam Dahri, Adeel Hayder Arain (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The present study aims to identify the causes and symptoms of penile fracture, as well as the postoperative results. Study Design: Prospective study Place and Duration: Present study was conducted at Department of Urology, LUMHS, Jamshoro, during from the period October 2022 to September 2023. Methods: A total of 36 individuals with penile fractures were included in this investigation. Included patients ranged in age from 18 to 45 years. Upon obtaining informed written consent, comprehensive demographic data on the recruited patients was gathered, including age, body mass index, residence, and marital status. The causes and clinical characteristics of the fracture were evaluated. Patients had surgery, and the success rate was evaluated. The post-treatment complication rate among enrolled cases was also determined. The data was analyzed using SPSS version 23.0. Results: The mean age was 31.4±10.86 years and BMI 23.62±3.89 kg/m2. Most patients were married 29 (80.56%) and unmarried 7 (19.44%). 20 (55.56%) patients had resided in urban and 16 (44.44%) in rural areas. 25 (69.44%) fractures were caused by coital, 6 (16.67%) by masturbation, and 5 (13.89%) by sleep manipulation. The most prevalent symptoms were deformity, edema, detumescence, and crackling. Right corpus was most common tunical tear 29 (80.56%) and proximal location 27 (75%). Success percentage was 88.89% in 32 instances. Post-operative complications included plaques/nodules, curvature, erectile dysfunction, discomfort, and edema in 7 (19.44%) cases. Conclusion: Prompt initial surgical treatment of a penile fracture can restore normal erection function and prevent serious complications. Common results of this surgery include rapid erectile function restoration and shorter hospital stays. Keywords: Penile Fracture, Causes, Surgery, Complications